Impacts of Intraguild Predation on Arctic Copepod Communities - Dufour, Karolane; Maps, Frédéric; Plourde, Stéphane; Joly, Pierre; Cyr, Frédéric (Frontiers in Marine Science, 2016)
Communities of large copepods form an essential hub of matter and energy fluxes in Arctic marine food webs. Intraguild predation on eggs and early larval stages occurs among the different species of those communities and it has been hypothesized to impact its structure and function. In order to better understand the interactions between dominant copepod species in the Arctic, we conducted laboratory experiments that quantified intraguild predation between the conspicuous and omnivorous Metridia longa and the dominant Calanus hyperboreus. We recorded individual egg ingestion rates for several conditions of temperature, egg concentration and alternative food presence. In each of these experiments, at least some females ingested eggs but individual ingestion rates were highly variable. The global mean ingestion rate of M. longa on C. hyperboreus eggs was 5.8 eggs ind-1 d-1, or an estimated 37% of M. longa daily metabolic need. Among the different factors tested and the various individual traits considered (prosome length, condition index), only the egg concentration had a significant and positive effect on ingestion rates. We further explored the potential ecological impacts of intraguild predation in a simple 1D numerical model of C. hyperboreus eggs vertical distribution in the Amundsen Gulf. Our modelling results showed an asymmetric relationship in that M. longa has little potential impact on the recruitment of C. hyperboreus (< 3% egg standing stock removed by IGP at most) whereas the eggs intercepted by the former can account for a significant portion of its metabolic requirement during winter (up to a third).